Discrete wavelet transform and probabilistic neural networks algorithm for identification of fault locations on transmission systems - Ngaopitakkul, A.; Kunakorn, A.; Bunjongjit, S. (My University, 2004)
This paper proposes a new algorithm for detecting faults in an electric power transmission system. The Discrete Wavelet Transform (DWT) and probabilistic neural network (PNN) are used in order to detect the high frequency components and to identify fault locations on the transmission system. Simulations and the training process for the neural network are performed using ATP/EMTP and MATLAB. It is found that the proposed algorithm gives satisfactory results, and will be very useful in the development of a power system protection scheme. © 2004 IEEE.
Keywords: ATP/EMTP; Discrete wavelet transform; Fault; Probabilistic neural network